Analisis Kebijakan Impor di Indonesia Menurut Perspektif Islam - Qayyimah, Fathiyah Muslimah; Huda, Nurul (ITB AAS INDONESIA Surakarta, 2024)
The analysis of import policy in Indonesia from an Islamic perspective highlights the complexity of the interaction between economic aspects and religious values in the formation of public policy. In this context, it is important to consider how import policies can reflect Islamic principles that prioritize social justice, cooperation, and general welfare. The purpose of this study is to consider how import policy, as an important instrument in a country's economy, can be interpreted through an Islamic lens. This research utilizes a descriptive qualitative method. The results of this study provide an in-depth understanding of the impact of import policies on economic justice, economic self-reliance, and international cooperation, and highlight the compatibility of these policies with Islamic principles. The protection of local producers, promotion of fair international cooperation, and increased participation of Islamic scholars and economists in the decision-making process are key steps in designing a more inclusive and sustainable import policy that takes into account the interests of society.